2016
DOI: 10.1039/c6ob01544a
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphorus-mediated N–N bond formation: facile access to 3-amino-2H-indazoles

Abstract: A convenient and efficient strategy has been devised to access 3-amino-2H-indazole derivatives in two steps from readily available starting materials. The conversion of 2-nitrobenzonitriles to substituted benzamidines followed by an organophosphorus-mediated reductive cyclization and a subsequent N-N bond formation afforded 3-amino-2H-indazoles in good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…To explore the flexibility and robustness of our one‐pot methodology and to expand the substrate scope further, we applied our method towards the synthesis of 3‐amino‐2 H ‐indazoles 64 (Table ) through the reductive cyclization of N ‐substituted 2‐nitrobenzamidines 63 . Whereas a high excess amount of 5 equivalents of tributylphosphine as the organophosphorus reagent was previously required for an effective reaction, we could again decrease this by applying our standard reaction conditions by using 0.8 equivalents of phospholene oxide.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To explore the flexibility and robustness of our one‐pot methodology and to expand the substrate scope further, we applied our method towards the synthesis of 3‐amino‐2 H ‐indazoles 64 (Table ) through the reductive cyclization of N ‐substituted 2‐nitrobenzamidines 63 . Whereas a high excess amount of 5 equivalents of tributylphosphine as the organophosphorus reagent was previously required for an effective reaction, we could again decrease this by applying our standard reaction conditions by using 0.8 equivalents of phospholene oxide.…”
Section: Resultsmentioning
confidence: 99%
“…General procedure for the synthesis of 3‐amino‐2 H ‐indazoles : Benzamidine derivatives 63 were synthesized according to a known procedure . Diphenylsilane (317.1 μL, 1.72 mmol) was added to a solution of benzamidine derivative 63 (0.33 mmol) and 3‐methyl‐1‐phenyl‐2‐phospholene 1‐oxide (101.8 mg, 0.53 mmol) in dry toluene (4 mL) in a sealed tube at RT.…”
Section: Methodsmentioning
confidence: 99%
“…Nazaré et al [ 29 ] demonstrated an organophosphorus-mediated reductive cyclization and a subsequent N-N bond formation of substituted benzamidines 40 to construct 3-amino-2 H -indazoles 41 ( Scheme 14 a). The substituted benzamidines 40 were synthesized from 2-nitrobenzonitriles 39 through a two-step sequence involving a trimethylaluminium-mediated conversion.…”
Section: Synthesis Route For Indazole Derivativesmentioning
confidence: 99%
“…While unsubstituted 1 H ‐indazoles and N1‐substituted‐1 H ‐indazoles are well represented in the chemical space and in particular populating the kinase ligand space, the 2 H ‐indazole framework is only rarely described. This is mainly attributed to the fact that until very recently, only a few direct methods allowed regioselective access to N2‐substituted 2 H ‐indazoles …”
Section: Resultsmentioning
confidence: 99%